2021
DOI: 10.3389/pore.2021.1609976
|View full text |Cite|
|
Sign up to set email alerts
|

Associations of Porphyromonas gingivalis Infection and Low Beclin1 Expression With Clinicopathological Parameters and Survival of Esophageal Squamous Cell Carcinoma Patients

Abstract: Purpose: The present study focused on exploring the associations of Porphyromonas gingivalis (P. gingivalis) infection and low Beclin1 expression with clinicopathological parameters and survival of esophageal squamous cell carcinoma (ESCC) patients, so as to illustrate its clinical significance and prognostic value.Methods: Immunohistochemistry (IHC) was used to detect P. gingivalis infection status and Beclin1 expression in 370 ESCC patients. The chi-square test was adopted to illustrate the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Cells of each group were routinely cultured in six-hole plates at 1 × 10 3 cells/2 mL for 1 week. After fixation with formaldehyde and staining with crystal violet, the clones were photographed and counted …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cells of each group were routinely cultured in six-hole plates at 1 × 10 3 cells/2 mL for 1 week. After fixation with formaldehyde and staining with crystal violet, the clones were photographed and counted …”
Section: Methodsmentioning
confidence: 99%
“…Then cells were photographed at 0 h after scratching and 24 h at the unaltered location after being conventional cultured. The cell mobility of each group was measured and calculated …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…P. gingivalis exerts toxic effects of adhesion to and invasion of gingival epithelial cells, interfering with the normal physiological metabolism of cells and inhibiting programmed cell death [15]. In recent years, an increasing number of studies have shown that P. gingivalis is closely related to a variety of malignant tumours [16][17][18][19]. In this paper, recent research progress on the correlation and pathogenesis between P. gingivalis and ESCC is reviewed to provide aid for clinical practice.…”
Section: Introductionmentioning
confidence: 99%